Determinan Arus Kas Perusahaan Manufaktur Indeks LQ 45 yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018 - 2023 - Annisa Lestari; Adler Haymans Manurung; Edward Efendi Silalahi; Muhammad Richo Rianto; Jhonni Sinaga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Free cash flow is a way to calculate the remaining cash flow that is not used for investment or operations. The purpose of this study is to determine how the variables net profit, depreciation, and changes in investment have an effect on free cash flow recorded on the Indonesia Stock Exchange during the period 2018-2023. This study uses a quantitative approach method. The results of this study indicate that Net Profit has a positive and significant effect on Free Cash Flow, Depreciation has a positive and significant effect on Free Cash Flow, and Changes in Investment have a negative and insignificant effect on Free Cash Flow.